Initial treatment of patients with primary breast cancer: evidence, controversies, consensus : spectrum of opinion of German sepecialists at the 15th International St. Gallen Breast Cancer Conference (Vienna 2017) = Erstbehandlung von Patientinnen mit primärem Mammakarzinom : Evidenz, Kontroversen, Konsens : Meinungsbild deutscher Experten zur 15. Internationalen St. Gallen-Konsensuskonferenz (Wien 2017) - Untch, Michael; Huober, Jens; Jackisch, Christian; Schneeweiss, Andreas; Brucker, Sara; Dall, Peter; Denkert, Carsten; Fasching, Peter Andreas; Fehm, Tanja; Gerber, Bernd; Janni, Wolfgang; Kühn, Thorsten; et al. (Geburtshilfe und Frauenheilkunde, 2017)
The St. Gallen International Consensus Conference on the treatment of patients with primary breast cancer has been held regularly (every second year in the last six years) for more than 30 years. This year, the findings of the International St. Gallen Consensus Panel and their implications for clinical practice were again discussed by a German working group of leading breast cancer specialists. Five of the breast cancer specialists from Germany were also members of this yearʼs St. Gallen panel. A comparison between the St. Gallen recommendations and the annually updated treatment guidelines of the Gynecologic Oncology Group (AGO 2017) and the S3-guideline agreed upon in 2017 is useful. The recommendations of the St. Gallen panel represent an international cross-section of opinions of experts from different countries and different disciplines, while the S3-guideline and AGO guidelines are evidence-based. The motto of this yearʼs 15th St. Gallen Conference was “Escalating and De-Escalating”. The rationale behind this concept was to promote more individualized treatment and thereby reduce overtreatment as well as undertreatment.
Gesehen am 30.10.2018